A NATIONAL STUDY OF SOCIAL NETWORKS AND PERCEPTIONS OF HEALTH AMONG URBAN AMERICAN INDIAN/ALASKA NATIVES AND NON-HISPANIC WHITES - BASSETT, DEBORAH R. (2014)
Using data from The National Epidemiologic Survey on Alcohol and Related Conditions, the strength of social networks and the association of self-reported health among American Indians and Alaska Natives (AI/AN) and non-Hispanic Whites (NHW) were compared. Differences in social network–health relationships between AI/ANs and NHWs were also examined. For both groups, those with fewer network members were more likely to report fair or poor health than those with average or more network members, and persons with the fewest types of relationships had worse self-reported health than those with the average or very diverse types of relationships. Furthermore, small social networks were associated with much worse self-reported health in AI/ANs than in NHWs.